Diseño de un sistema híbrido de generación de energía eléctrica a partir de energías renovables en la isla de San Andrés (2024)
The present study was based on the design of a hybrid system for generating electrical energy from renewable sources such as wind energy and ocean thermal gradient for the island of San Andrés, Colombia. Within which the electrical consumption of the Island of San Andrés was determined with the values ​​obtained from the island's electrification plant and the data collected from the IPSE, where there is a daily energy value of 36,754 kWh and a total consumption per year in 2023 of 495,546 kWh. The wind resource and oceanic thermal gradient are characterized; for the wind resource, data from the Colombian Wind Atlas are collected, extracting the shape and scale parameters, in order to construct the probability distribution of wind speed, in order to carry out the analysis of each of the segmented speeds in the months of the year, resulting in low wind speeds in the months of October and December and high wind speeds in the months of March, November and February.